Cutaneous vasculitis and IgA glomerulonephritis in ankylosing spondylitis. Issue 1 (January 1993) - Beauvais, C; Kaplan, G; Mougenot, B; Michel, C; Marinho, E
Abstract : Two patients with ankylosing spondylitis were found to have IgA nephropathy and leucocytoclastic cutaneous vasculitis. Immunofluorescence showed perivascular deposition of IgA in the skin of one patient and in the mesangium of both patients. Such an association has been reported only once before. This supports the concept of abnormal IgA immune stimulation in the pathogenesis of ankylosing spondylitis.